2014
DOI: 10.4103/0973-1296.133232
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract from taxus baccata inhibits adenosine deaminase activity significantly in cancerous and noncancerous human gastric and colon tissues

Abstract: Objective:To investigate possible effects of aqueous taxus baccata extract on adenosine deaminase (ADA) activity in cancerous and noncancerous human tissues and to clarify mechanism(s) of its anticancer potential.Materials and Methods:Cancerous and noncancerous human gastric and colon tissues were used in the study. The extracts were prepared in distilled water. Before and after treatment with the extracts, ADA activities in the tissue homogenates were measured.Results:ADA activity was found to be higher in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Aqueous extract from Taxus baccata inhibited adenosine deaminase (ADA) activities in both cancerous and noncancerous human gastric and colon tissues significantly. The ADA activities in human cancerous gastric and colon tissues were inhibited by 79.5 and 91.4%, respectively, in the study 14 . Aqueous and ethanolic extract of Taxus baccata leaf and Indian cow urine distillate showed synergistic anticancer effects as evidenced from good cytotoxicity and good recovery in clinico pathological parameters of Diethyl Nitrosamine induced hepatic cancer in mice 15 .…”
Section: Introductionmentioning
confidence: 83%
“…Aqueous extract from Taxus baccata inhibited adenosine deaminase (ADA) activities in both cancerous and noncancerous human gastric and colon tissues significantly. The ADA activities in human cancerous gastric and colon tissues were inhibited by 79.5 and 91.4%, respectively, in the study 14 . Aqueous and ethanolic extract of Taxus baccata leaf and Indian cow urine distillate showed synergistic anticancer effects as evidenced from good cytotoxicity and good recovery in clinico pathological parameters of Diethyl Nitrosamine induced hepatic cancer in mice 15 .…”
Section: Introductionmentioning
confidence: 83%
“…In our previous studies, we have found that extracts prepared from some plants like Taxus brefolia [48], Sillybum marianum [49] and Curcuma longa [50] could make significant inhibitions on the ADA activities in cancerous human gastric and colon tissues. In this study, we have also obtained similar results with Echinacea for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extract from T. baccata inhibits adenosine deaminase (ADA) activity significantly in cancerous and noncancerous human gastric and colon tissues (Durak et al, 2014). In addition to other proposed mechanisms, accumulated adenosine due to the inhibition of ADA enzyme might also play a part in the anticancer properties of Taxus species.…”
Section: Anticancer Activitymentioning
confidence: 99%